The Last Days: Haunting futures and parasitic subjectivities in the age of media franchising - Per Israelson (Barnelitterært Forskningstidsskrift)
The dark and catastrophic futures of dystopian and post-apocalyptic YA fiction are often perceived of as critiques of late capitalist society, presenting an alternative to the status quo of what Mark Fisher once termed «capitalist realism». However, as these narratives at the same time comport according to the feedback and control mechanisms of genre conventions and popular media franchises, they also reproduce, within the system of genre and franchise structures, the very conditions under which creativity and, in extension, future worlds can emerge. The participatory aesthetics of dystopian and post-apocalyptic YA fiction, in which co-creation of other worlds is integral, here becomes a matter of adhering to the regulatory feedback of a system of control. Hence, the alternative futures presented by critical dystopias are already lost to the capitalist present. Nevertheless, this paper argues that one possible solution to the lost futures of capitalist realism can be found in the ecological concept of sympoiesis and in a parasitic notion of subjectivity. Discussing Scott Westerfeld’s two novels Peeps and The Last Days, it is suggested that the future of, and for, creativity lies in the haunting of parasitic infections.